Optimal coordination of buildings and microgrids by an aggregator: a bi-level approach. Issue 2 (2020) - Ferro, Giulio; Minciardi, Riccardo; Parodi, Luca; Robba, Michela; Rossi, Mansueto
Abstract: The introduction of renewables, distributed generation, microgrids, electric vehicles, and new market actors, such as aggregators, have led to a remarkable change in the power network. To address the issues that such a profound modification implies on a modern energy system, here a new hierarchical architecture is presented. Specifically, the proposed approach considers the case of an aggregator of consumers in the balancing market, in which incentives for local users (i.e., microgrids, buildings) are considered as well as flexibility assessment for demand response, and CO2 emissions. The main innovation is related to the overall architecture and to the formalization of the upper level decision problem that aims at coordinating local users in a democratic way, while, at the lower level, consumers want to track the aggregator's reference values performing demand response programs. The approach is applied to a real case study.